POTENSI JIGSAW IV SEBAGAI STRATEGI PEMBELAJARAN BIOLOGI YANG MEMBERDAYAKAN KETERAMPILAN METAKOGNISI PADA KEMAMPUAN AKADEMIK BERBEDA - Suratno, Suratno (Prosiding Seminar Biologi, 2010)
ABSTRACT This study aims at finding out the effect of the learning strategy Jigsaw IV toward the metacognition skill  and the effect of the academic ability toward the metacognition skill This study was quasi experimental design with factorial 4 x 2. The procedure of the experimental study was pretest-posttest nonequivalent control group design. This study included independent and dependent variables. Independent variables was learning strategy Jigsaw, lower and upper acadmic ability.. Dependent variables were the metacognition skill The metacognition skill was measured through rubric. Findings showed that the Jigsaw IV learning strategy affected toward the metacognition skill Key words: Jigsaw, metacognitive skills, upper academic ability, lower academic ability